Quantum light-induced nonadiabatic phenomena in the absorption spectrum of formaldehyde: full- and reduced-dimensionality studies - Fábri, Csaba; Lasorne, Benjamin; Halász, Gábor J.; Cederbaum, Lorenz S.; Vibók, Ágnes (The journal of chemical physics, 2020)
The coupling of a molecule to a cavity can induce conical intersections of the arising polaritonic potential energy surfaces. Such intersections give rise to the strongest possible nonadiabatic effects. By choosing an example that does not possess nonadiabatic effects in the absence of the cavity, we can study, for the first time, the emergence of these effects in a polyatomic molecule due to its coupling with the cavity taking into account all vibrational degrees of freedom. The results are compared with those of reduced-dimensionality models, and the shortcomings and merits of the latter are analyzed.
Gesehen am 11.02.2021